2011
DOI: 10.1371/journal.pone.0026734
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent K. Pneumoniae Secretes More and More Active Iron-Acquisition Molecules than “Classical” K. Pneumoniae Thereby Enhancing its Virulence

Abstract: BackgroundA new hypervirulent (hypermucoviscous) clinical variant of Klebsiella pneumoniae (hvKP) has emerged over the last decade. Our goal is to identify new mechanisms, which increase the virulence hvKP compared to “classic” K. pneumoniae (cKP).Methodology/Principal FindingsVarious growth assays were performed in human ascites, human serum, and laboratory medium with the hvKP strain hvKP1 (wt), randomly chosen blood isolates of cKP strains (cKP1-4), and mutant constructs deficient in the secretion of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 57 publications
2
99
0
2
Order By: Relevance
“…The discrepancy in the frequency of the rmpA gene between CC65-K2 and GL65-K2 may be explained by the housekeeping genes of MLST, which are located on a chromosome (21), unlike the rmpA gene, which is located on a plasmid. The string test indicated that 66.7% of the GL65-K2 strains had the HV phenotype, which was identified as an important virulence factor for K. pneumoniae in mouse models (31,32). Recent genetic and phenotypic characterizations showed that the genetic background, rather than the capsular serotype, was associated with the virulence of K. pneumoniae (24).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in the frequency of the rmpA gene between CC65-K2 and GL65-K2 may be explained by the housekeeping genes of MLST, which are located on a chromosome (21), unlike the rmpA gene, which is located on a plasmid. The string test indicated that 66.7% of the GL65-K2 strains had the HV phenotype, which was identified as an important virulence factor for K. pneumoniae in mouse models (31,32). Recent genetic and phenotypic characterizations showed that the genetic background, rather than the capsular serotype, was associated with the virulence of K. pneumoniae (24).…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this goal, most bacteria produce chemically diverse siderophores (20), small-molecule chelators with remarkably high association constants for Fe 3ϩ , that enable them to acquire iron in iron-depleted environments, such as the human host. Interestingly, we have shown that hvKP is characterized by a 6-to 10-fold increase in siderophore activity compared to cKP strains (21,22). Further, and surprisingly, aerobactin accounted for Ͼ90% of the siderophore activity despite the ability of hvKP to produce multiple siderophores (21).…”
mentioning
confidence: 84%
“…The mouse subcutaneous (SQ) challenge and pneumonia models have been described (21,22,27). Animal studies were reviewed and approved by the University at Buffalo-SUNY and Veterans Administration Institutional Animal Care Committee.…”
Section: Methodsmentioning
confidence: 99%
“…When considering these infections, it is important to recall that HV strains are far more likely to cause community-acquired and systemic infections in otherwise healthy individuals, but for the most part, these strains are geographically limited to Taiwan and Southeast Asia. In contrast, classical strains of K. pneumoniae typically cause serious nosocomial infections or UTIs and can be found worldwide (41,(48)(49)(50). While there is a broad overlap of the types of infections caused by classical versus HV strains, some diseases are far more likely to be caused by HV than classical strains.…”
Section: Infections Caused By K Pneumoniaementioning
confidence: 99%